An Analytical Study of Difficulties in Learning the Passive Voice/structure - Assem Alqarni (Journal of Arts, Literature, Humanities and Social Sciences, 2023)
Understanding the active-passive structure is essential in learning English grammar as many students struggle with comprehension, particularly in conversion of active to passive voice and vice versa. This paper identifies and analyzes the primary difficulties faced by second semester students in changing active voice to passive structure. The study basically adopts a qualitative approach (with some calculations), and gathers data from students enrolled in the foundation year Diploma program of a Saudi public university, as well as insights from a English language instructor. Data collection methods include observation, documentation, and interviews. Analysis follows the model proposed by Miles and Huberman (1994), relying on the reduction, display, and verification of data. The study reveals that the most common difficulties among students include challenges in determining the subject, utilizing helping verb ’be’, and using the third form (past participle) while changing into passive voice. Notably, more predominant challenge lies in comprehending the past and future tense, often exacerbated by reliance on dictionaries. From these findings, it is concluded that while some students exhibit little understanding of passive voice, others require improvement in English grammar comprehension especially the passive voice. A compatible strategy is always required for handling such learning issues.